Science, Politics, Law, and the Arc of the Clean Water Act: The Role of Assumptions in the Adoption of a Pollution Control Landmark - Robert L. Glicksman; Matthew R. Batzel (Washington University Journal of Law & Policy, 2010)
This Article examines the assumptions upon which Congress relied in enacting the Clean Water Act ("CWA") and the extent to which these assumptions have been borne out or belied as the federal and state governments have implemented their CWA responsibilities in the quest to achieve acceptably clean water. Part I briefly traces the development of federal water pollution control legislation before 1972, highlighting the deficiencies that contributed to the need for a new approach in 1972. Part II examines the scientific and technical, political, and legal assumptions that helped shape the 1972 CWA in order to determine whether the failure to achieve fully the statute‘s goals is inherent in the statute‘s design or is the result of the law‘s incomplete implementation. Part III provides an assessment of how water quality conditions today compare both with those that existed in 1972 and with the goals that Congress identified in the CWA. The Article concludes by speculating about the future direction of water pollution control law. We conclude that a surprisingly large share of the assumptions upon which Congress built the CWA were valid and have helped to make the statute an environmental success story. The statute‘s failure to perform even more admirably than it has is due largely to a lack of legislative clarity in addressing the role of wetlands in preserving the integrity of aquatic ecosystems and to Congress‘s unwillingness to adopt, or force the states to adopt, measures to control nonpoint source pollution.
Keywords: Water pollution -- Law & legislation; Legislative histories; Water pollution; Wetlands; United States. Environmental Protection Agency; Federalism; Water pollution control; Clean Water Act of 1977